Religious moderation: Muhammadiyah inclusivism and syncretic Islam in Javanese culture in Yogyakarta - Muhammad Syamsuddin; Kurniatul Jannah; Novia Indriani; Aditia Pramudia Sunandar; Muhammad Insan Fathin; Benni Setiawan; Iqbal Arpannudin (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
Differences in understanding between religions and cultures characterise the emergence of intolerance in society. These conditions can contribute to the breakdown of religious life and result in subjective interpretations of truth that disregard others' perspectives. The research method used a mixed method with a sequential exploratory model. Data collection techniques included interviews, observations, literature studies (qualitative), and questionnaires (quantitative). This study aims to reveal the dynamics of cultural da'wah, the process of Muhammadiyah internalisation, and the relationship between Muhammadiyah and syncretic Islam in shaping the value of tolerance in Yogyakarta. The results of the study show several things, namely 1) there are dynamics of cultural da'wah described by the concepts of hablumminallah and hablumminannas with examples of each entity's attitude towards the night of Suro; 2) there is involvement of each entity in Muhammadiyah activities with conservative teaching materials and adaptive methods, as demonstrated by the processes of acculturation, assimilation, and accommodation in each entity's religious activities; and 3) the phenomena observed in this case study illustrate the relationship between Muhammadiyah and Syncretic Islam in shaping the value of tolerance in Yogyakarta. The relationship between the two can fulfil the indicators of the active tolerance model by being able to coexist peacefully and strive to respect diversity.